POLA PENDIDIKAN BUDI PEKERTI DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA-SISWI KATOLIK - Augustine, Brigitta Alvera; Permana, Natalis Sukma (Lembaga Penelitian STKIP Widya Yuwana, 2024)
Character of education is an effort to educate students so that the students have noble attitudes and behavior. In fact, this education still has not achieved the objectives of the establishment of the program. From the results of initial observations at Junior High School I Wonogiri and Kanisius Wonogiri Middle school, it was found that there were several degradations of moral values which had an impact on reducing student motivation. Therefore, this research focused on digging deeper into how both public and private schools apply patterns of character education as a school effort to help increasing student motivation. The research method used in this research was to use a qualitative research method using a comparative descriptive approach. The results of study showed that in the implementation of character education, Junior High School I Wonogiri applied moral values as a whole while the three main values emphasized by Kanisius Wonogiri Middle School were more religious values, honesty values, and social care values; in terms of school strategies and methods, the teacher's approach and the evaluation used both have similarities and differences. The results of the study show that the two schools have their own characteristics which are tailored to the vision and mission of each school.